Description of six new species of Anomalini from Costa Rica (Coleoptera: Scarabaeidae: Rutelinae) - Filippini, Valentina; Galante, Eduardo; Micó, Estefanía (Zootaxa, 2015)
Four new species of Anomala Samouelle and two new species of Callistethus Blanchard (Coleoptera: Scarabaeidae: Rutelinae: Anomalini) from Costa Rica are described: A. aglaos new species, A. estrella new species, A. inbio new species, A. pincelada new species, C. ruteloides new species, and C. yalizo new species. A distribution map of each species is given and the male genitalia (aedeagus and endophallus) of the species described and similar species are illustrated.